Pengaruh Brand Equity dan Online Customer Reviews (OCRs) terhadap Keputusan Pembelian Produk The Originote pada Aplikasi Tiktok Shop - Gabriella Niken A.S; Abdul Waris (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
Tiktok is the only social media that is widely used by shoppers to see product reviews before deciding to buy. One of the most searched content is beauty products. Research was conducted to determine the effect of brand equity and online customer reviews (OCRs) on purchasing decisions for The Originote products on the Tiktok Shop Application. This study focuses on The Originote skincare using quantitative methods. The sample used was Generation Z in Malang City with a multistage random sampling technique. Data analysis includes instrument testing, descriptive, classical assumption testing and hypothesis testing. The results of the study show that both brand equity and OCRs variables significantly contribute to purchasing decisions. Partially and simultaneously, both variables have a significant influence on purchasing decisions. To improve and strengthen brand equity, The Originote needs to upgrade the outer packaging so that the product is protected from impact. On the other hand, to improve online customer reviews, The Originote needs to create an SOP for admins to reply to customer reviews.